Features of Oxygen Extraction Ratio and Temperature Homeostasis during Early Postoperative Period after Major Abdominal Surgery - Musaeva TS (Global Journal of Perioperative Medicine - Peertechz Publications, 2017)
In some situations, tissue hypoxia may exist despite normal values obtained by conventional haemodynamic monitoring such as arterial blood pressure, central venous pressure, heart rate, and urine output. The study was performed in early postoperative period after major abdominal surgery in 160 patients and was conducted in the following stages: 1- admission from operating room; 2 - in 1-3 hours; 3 - 4-7 hours; 4 - 8-12 hours; 5 - after 13-24 hours after the surgery. Depend on rate of oxygen extraction index (ERO2) patients was divided in four groups depending on ERO2 on admission: group 1 (n=44) - low ERO2 (< 21%) followed by recovery to normal levels to stage 2-3 (ERO2 = 22-32%), group 2 (n=42) - normal level ERO2 (22-32%) in all the stages, group 3 (n=40) - high levels ERO2 (>33%) with recovery to normal levels to stage 2, group 4 (n=34) - high ERO2 (> 35%) in all the stages. Central hemodynamic, gas exchange, metabolic rate and temperature parameters were assessed. Maintaining an adequate tissue oxygenation is the cornerstone of metabolic response and postoperative recovery in patient after major abdominal surgery. Oxygen extraction index at admission to ICU after surgery can be normal (26.25% of patients), reduced (27.5% of patients) or high (46.25% of patients). When oxygen extraction ratio is reduced metabolic recovery occurs classically after 4-7 hours; when ERO2 is elevated - after 8-12 hours. For patients with high oxygen extraction ratio marked venous hypoxemia is typical, which recovery to 4-12 hours post-surgery.